Pengaruh Strategi Pemasaran Asuransi Mikro terhadap Kesejahteraan UMKM di Indonesia - Muhammad Andre Alkahfi; Nuri Aslami (VISA: Journal of Vision and Ideas, 2021)
The purpose of this research is to explain a phenomena that happened in the Indonesian microinsurance business. Using the case study technique, we observed that microinsurance is still difficult to develop based on the overall population of Indonesians. If the main idea of micro insurance is applied, micro insurance products are still widely available in big cities but have yet to reach low-income individuals or UMKM. A breakthrough is necessary to produce microinsurance. This microinsurance business must be developed through a network of local communities, which are usually located in the lower middle class, or UMKM. Aside from that, marketers must have a set of tools at their disposal, such as a suitable ICT-based market (community) database. As a result, any microinsurance business formed must be targeted to the demands of the Indonesian government, such as microinsurance for agricultural, livestock, and fisherman, particularly in rural regions. Meanwhile, the most enticing micro insurance enterprises for metropolitan regions are personal accidents, property, and motor and vehicles. Keywords: Micro, UMKM, Insurance, Marketing.